Article Commentary: Where is the Theoretical Basis for Understanding and Measuring the Environment for Physical Activity? - N.M. Nelson; A. Wright; R.G. Lowry; N. Mutrie (SAGE Publishing, 2008)
Researchers are beginning to explore environmental correlates to further the field of physical activity research. Before interventions and experimental investigations can be undertaken, it is necessary to identify specific environmental features that are consistent correlates of physical activity. There has been a plethora of research measuring such cross-sectional associations since this field came to the fore in 2003. This paper posits that it is time for researchers to evaluate the state of knowledge, and suggests that future developments in this field focus on the theoretical bases for (i) measurement of the environment and (ii) understanding the links between perceptions of the environment and behaviour through psychological theories of cognition. Key theories considered include social ecology and the theory of planned behaviour. It is suggested that with a continued absence of a common conceptual framework, vocabulary and measurement tools the majority of studies may remain at a correlates stage. In highlighting issues with current methodologies, this commentary encourages more grounded theoretical approaches to the study of the environment and physical activity.